The effectiveness of the language experience approach and extensive reading approach in improving the narrative writing skills of upper primary school students / Siti Mariam Mohammad Iliyas, Amutha Kuppa and Thilakavathv Vellasamv - Mohammad Iliyas, Siti Mariam; Kuppa, Amutha; Vellasamy, Thilakavathy (Faculty of Information Management, 2015)
Writing is a means of extending and deepening students' knowledge and it acts as a tool for learning subject matter (Keys, 2000; Shanahan, 2004; Sperling 8c Freedman, 2001).The skill of writing is taught to enable learners to express their ideas clearly on paper in legible handwriting. In this component, the focus is on.developing learners' writing ability beginning at the word and phrase levels and progress to the sentence and paragraph levels. This study sets out to investigate the effectiveness of using Language Experience Approach and Extensive Reading Approach as approaches to improve writing ability among the pupils. Quantitative analysis was utilized following the data gathered from both experimental and treatment groups. The findings suggest that the incorporation of these approaches in language classroom is highly recommended based on the significantly positive effect that they have towards improving language learners' skills.